DAMPAK ALIH FUNGSI LAHAN MENJADI TAMBAK UDANG TERHADAP EKONOMI MASYARAKAT TAHUN 2016-2022, NAGARI KATAPIANG KECAMATAN BATANG ANAI - Rahmawati, Zahara; Ahyuni, Ahyuni (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
This research aims to: 1) determine changes in land use in 2016-2022. 2) Knowing the impact of land conversion into shrimp ponds on the economy of the community in Nagari Katapiang, Batang Anai District, Padang Pariaman Regency. This research is quantitative research using the overlay method and percentage analysis techniques. The results of this research show that: 1) Land use has decreased significantly, namely swamps with an area of 1.8 Ha in 2016, in 2022 it has an area of 0 Ha. The use of plantation land experienced a significant increase in 2016-2019 with an area of 62.8 Ha, then increased in 2022 with an area of 4.3 Ha. 2) Increase in income of the trading community after the existence of shrimp ponds with a range of 4,000,000-15,000,000 compared to previously around 2,000,000-3,000,000 per month. The impact on labor absorption from Nagari Katapiang amounted to 21% of the 100 shrimp pond worker respondents, and the income spent in Nagari Katapiang amounted to 3% -50%.